Crosslinked Coating Improves the Signal‐to‐Noise Ratio of Iron Oxide Nanoparticles in Magnetic Particle Imaging (MPI). Issue 5 (1st April 2020) - Horvat, Sonja; Vogel, Patrick; Kampf, Thomas; Brandl, Andreas; Alshamsan, Aws; Alhadlaq, Hisham A.; Ahamed, Maqusood; Albrecht, Krystyna; Behr, Volker C.; Beilhack, Andreas; Groll, Jürgen
Abstract: Magnetic particle imaging is an emerging tomographic method used for evaluation of the spatial distribution of iron‐oxide nanoparticles. In this work, the effect of the polymer coating on the response of particles was studied. Particles with covalently crosslinked coating showed improved signal and image resolution. Abstract : Magnetic particle imaging is an emerging tomographic method used for evaluation of the spatial distribution of iron‐oxide nanoparticles. In this work, we evaluated the effect of a hydrophilic polymer coating on the particle response. We show that covalently crosslinked coatings lead to improved signal to noise ratios and better image resolution.